Everyday sexism [book club bag] - Bates, Laura, 1986- (Thomas Dunne Books, St. Martin's Griffin, 2016)
In a culture that's driven by social media, women are using this online space to come together, share their stories and encourage a new generation to recognise the problems that women face. This book is a call to arms in a new wave of feminism, and it proves sexism is endemic - socially, politically and economically - but women won't stand for it.